2D Joint Inversion of Gravity and Magnetic Data to Evaluate a Geological Structure in Tanimbar Island - Arkanu Andaru; Praditiyo Riyadi; Muhammad Nafian (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
The need for hydrocarbon energy, especially oil and gas, requires continuous exploration of hydrocarbon reserves, especially in eastern Indonesia. Tanimbar Islands, Maluku was chosen to be the research area because of its complex subsurface geology and is located on the fold thrust belt resulting from tectonic evolution. In this research, an innovation is carried out using joint inversion modeling by correlating physical parameters from two different geophysical data, which are gravity and geomagnetic. The purpose of this research is to determine the subsurface mapping of the research area, determine the density and susceptibility values of rocks, and determine the structural patterns that exist in the subsurface. The results of subsurface mapping of the Tanimbar Islands based on the results of Joint Inversion modelling have found a geological structure pattern in the form of a fold thrust belt due to the Banda Arc subduction zone. In section A-A', there is a sequence of fold thrust belt with 10 structural patterns, including 6 structures in the northwest-southeast direction and 4 structures in the northeast-southwest direction. In section B-B' there are 9 structural patterns in the northeast-southwest direction. High anomalies obtained density values ranging from 2.77 - 2.81 gr/cm3 and susceptibility ranging from 0.00125 - 0.0013 SI are thought to be caused by high basement in the form of volcanic rocks, while low anomalies obtained density values ranging from 2.45 - 2.49 gr/cm3 and susceptibility ranging from 0.0008 - 0.00085 SI are thought to be caused by thick sedimentary layers of the Batimafudi Formation.